Islamic State of Afghanistan : Staff Report for the 2004 Article IV Consultation and Second Review Under the Staff-Monitored Program. (IMF Staff Country Reports; Country Report ;, 2005)
This paper focuses on Afghanistan's 2004 Article IV Consultation and Second Review Under the Staff-Monitored Program. The authorities have made further progress in rebuilding institutions and implementing sound economic policies. They have maintained their commitment to fiscal discipline. Real GDP growth has been relatively strong, albeit from a very low base, and has slowed over the past 18 months, owing primarily to the negative impact of adverse weather conditions on agricultural production. Growth remained strong in the other sectors, especially in construction and services.